Emotional intelligence and individual differences in affective processes underlying task‐contingent conscientiousness. (18th September 2017) - Minbashian, Amirali; Beckmann, Nadin; Wood, Robert E.
Summary: Organisational researchers have recently begun to focus on the more dynamic aspects of personality in the workplace. The present study examines individual differences in the affective processes that underlie one such dynamic construct, task‐contingent conscientiousness. Using experience sampling data collected over 3 weeks from 201 managers, we show (a) that individuals differ substantially from each other in the paths that connect task demand, positive and negative affect, and conscientious behaviour; (b) that these individual differences cohere to define person types or classes that represent meaningful differences in the extent to which task‐contingent conscientiousness is mediated affectively; and (c) that emotional intelligence increases the likelihood of membership in classes that are characterised by affectively mediated effects. Theoretical implications of the findings are discussed with reference to the cognitive‐affective personality system model, research on the consequences of affect in the workplace, and the literature on emotional intelligence. Practical applications are suggested for managers who wish to use personality assessment for developmental purposes, especially in relation to facilitating behavioural change.